A cobalt arylphosphonate MOF - superior stability, sorption and magnetism (vol 55, pg 3053, 2019) - Zorlu, Yunus; Erbahar, Dogan; Cetinkaya, Ahmet; Bulut, Aysun; Erkal, Turan S.; Yazaydin, A. Ozgur; Beckmann, Jens (Royal Soc Chemistry, 2019)
[No abstract available]